Comparative analysis of the literary structure and theological motifs in John 2:1–12 and 20:1–18 - Nalewaj, Aleksandra (Studia Warmińskie, 2012)
The subject of this work is a comparative analysis of two John’s pericopes, namely the description of the sign at the wedding at Cana (2:1–12) and the story about the empty grave of Jesus, found in the morning of Easter (20:1–18). The starting point of our study is the suggestion presented by P.F. Ellis, that the literary structure of the Fourth Gospel is based on parallelisms. According to this concept, The Book of John was created on the basis of the laws of parallelism known in the ancient world, and not, as many commentators would like to see it, of the laws of narration. The author divides The Gospel of John into twenty-one units in a concentric structure of abcb’a’. The centre of the structure is the text 6:16–21. In the parallel scheme presented by Ellis, the unit 2:1–12 is complemented by the unit 20:1-18. The aim of this work is to present some literary as well as theological connections between the indicated texts. They support the view that the text was consciously worded in the above mentioned way and they allow for a more in-depth investigation into the author’s idea.